2007
DOI: 10.1002/ps.1498
|View full text |Cite
|
Sign up to set email alerts
|

The control of Asian rust by glyphosate in glyphosate‐resistant soybeans

Abstract: These results demonstrate the disease control activities of glyphosate against rust diseases in GR wheat and GR soybeans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
35
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
3
3
3

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 24 publications
4
35
0
Order By: Relevance
“…Some efficacy against Phakopsora pachyrhizi , the cause of Asian soybean rust, was reported in both greenhouse 215 and in the field on GR soybeans. 216 Tuffi Santos at al. 218 showed that glyphosate reduced the severity of rust caused by Puccinia pdisii on Eucalyptus grandis .…”
Section: Effects Of Glyphosate On Plant Disease In Glyphosate-resistamentioning
confidence: 99%
See 1 more Smart Citation
“…Some efficacy against Phakopsora pachyrhizi , the cause of Asian soybean rust, was reported in both greenhouse 215 and in the field on GR soybeans. 216 Tuffi Santos at al. 218 showed that glyphosate reduced the severity of rust caused by Puccinia pdisii on Eucalyptus grandis .…”
Section: Effects Of Glyphosate On Plant Disease In Glyphosate-resistamentioning
confidence: 99%
“…tritici ) 215,216 and leaf rust ( Puccinia triticina ) on GR wheat. 215,217 In these cases, it appears that glyphosate is acting directly as a fungicide.…”
Section: Effects Of Glyphosate On Plant Disease In Glyphosate-resistamentioning
confidence: 99%
“…There are more papers supporting this hypothesis than those that do not ( Table 2). Of special interest are the papers showing that glyphosate used on GR crops can have preventative and curative effects on rust diseases in GR maize, soybean, and alfalfa (Anderson and Kolmer, 2005;Dill et al, 2010;Feng et al, 2005Feng et al, , 2008Samac and Foster-Hartnett, 2012). Glyphosate also protected GR alfalfa from foliar diseases caused by Colletotrichum trifolii and Phoma medicaginis (Samac and Foster-Hartnett, 2012).…”
Section: Glyphosate-resistant Crops and Crop Diseasementioning
confidence: 96%
“…However, the speed of deactivation relative to glyphosate translocation and inhibition of EPSPS, especially at higher application rates and/or when sprayed at later plant development stages, is likely to be critical to overall tolerance. It has recently been shown that glyphosate is active against fungi, and the persistence of glyphosate in GT wheat and soybean, expressing an insensitive EPSPS, may help provide fungal disease suppression in these crops (Anderson and Kolmer 2005;Feng et al 2005Feng et al , 2008.…”
Section: Development Of Second-generation Gt Cropsmentioning
confidence: 99%